2020
DOI: 10.1111/jcmm.15802
|View full text |Cite
|
Sign up to set email alerts
|

Non‐coding RNAs in aortic dissection: From biomarkers to therapeutic targets

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 114 publications
0
32
0
3
Order By: Relevance
“…At present, TAD, like aortic aneurysm, has a high mortality rate worldwide. It is still urgent clinically to combine the new adjunctive approach within current interventions (1), and our research demonstrated that Sirt3 activation is expected to be a new target and adjuvant method for the treatment of TAD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At present, TAD, like aortic aneurysm, has a high mortality rate worldwide. It is still urgent clinically to combine the new adjunctive approach within current interventions (1), and our research demonstrated that Sirt3 activation is expected to be a new target and adjuvant method for the treatment of TAD.…”
Section: Discussionmentioning
confidence: 96%
“…Thoracic aortic dissection (TAD) is the most critical and catastrophic disease of all types of aortic syndrome, which has a rapid onset and a dangerous prognosis (1). When aortic intima has a rupture caused by various reasons, then blood flows into the aortic wall through the rupture, so that the middle layer is peeled from the adventitia to form two cavities.…”
Section: Introductionmentioning
confidence: 99%
“… 37 Recently identified as rising star of the ncRNAs, tsRNAs have been proven to be associated with regulation of RNA processing and protein translation. 38 Additional studies revealed that tRFs and tiRNAs fulfil an important function in multiple diseases. For example, high‐throughput sequencing revealed that tDR‐0009 and tDR‐7336 increased in hypoxia‐treated triple‐negative breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the roles of non‐coding RNAs (ncRNAs), including microRNAs, long non‐coding (lnc) RNAs and circulating (circ) RNAs, in disease pathogenesis, regulatory mechanisms and therapeutic applications have gradually become hot areas of research 90‐93 . Moreover, ncRNA has been shown to have an important regulatory role in CVD, 92,94‐105 tumours, 106 inflammation, 103,107 and heart development 108,109 . Increasing studies have shown that ncRNAs constitute potentially important players in biological regulation 110 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%